Effects of Epigallocatechin-3-Gallate on Autophagic Lipolysis in Adipocytes - Kim, Sang-Nam (Nutrients, 2017)
Previous studies demonstrated effects of green tea on weight loss; however, green tea-induced modulation of adipocyte function is not fully understood. Here, we investigated effects of the major green tea phytochemical, epigallocatechin-3-gallate (EGCG) on triglyceride contents, lipolysis, mitochondrial function, and autophagy, in adipocytes differentiated from C(3)H(10)T1/2 cells and immortalized pre-adipocytes in vitro. EGCG reduced the triglycerol content significantly in adipocytes by 25%, comparable to the nutrient starvation state. EGCG did not affect protein kinase A signaling or brown adipocyte marker expression in adipocytes; however, EGCG increased autophagy, as measured by autophagy flux analysis and immunoblot analysis of LC3B, ATG7, and Beclin1. EGCG treatment reduced mitochondrial membrane potential by 56.8% and intracellular ATP levels by 49.1% compared to controls. Although mammalian target of rapamycin signaling was not upregulated by EGCG treatment, EGCG treatment induced AMP-activated protein kinase phosphorylation, indicating an energy-depleted state. In addition, EGCG increased the association between RAB7 and lipid droplets, suggesting that lipophagy was activated. Finally, knockdown of Rab7 attenuated the EGCG-dependent reduction in lipid contents. Collectively, these results indicated that EGCG upregulated autophagic lipolysis in adipocytes, supporting the therapeutic potential of EGCG as a caloric restriction mimetic to prevent obesity and obesity-related metabolic diseases.